2007
DOI: 10.1002/app.26756
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies of poly(vinyl alcohol) films filled with a lanthanum/N‐ethylmorpholine complex

Abstract: Poly(vinyl alcohol) (PVA) films with different concentrations of lanthanum ions were prepared with a casting technique. The thickness of the prepared samples was 0.25 mm. Optical absorption and transmission measurements were performed for these samples. The ultraviolet-visible absorption spectra of pure PVA showed absorption bands at 200, 275, and 325 nm, which were assigned to the presence of carbonyl groups. The absorption spectra of doped PVA films showed an observable change in the band position with the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These OH groups can be a source of hydrogen bonding and hence assist the formation of polymer electrolytes (PEs). 5,6 However, monovalent ions like lithium capture must work in this field. The use of multivalent cations like magnesium will offer new technological applications with low cost and metal less reactive than lithium.…”
Section: Introductionmentioning
confidence: 99%
“…These OH groups can be a source of hydrogen bonding and hence assist the formation of polymer electrolytes (PEs). 5,6 However, monovalent ions like lithium capture must work in this field. The use of multivalent cations like magnesium will offer new technological applications with low cost and metal less reactive than lithium.…”
Section: Introductionmentioning
confidence: 99%
“…For the pure PVA (Fig. a), an absorption peak is found within 200–300 nm, which was attributed to π–π* transitions of CO and/or CC, which was originated from unsaturated bonds . The appearance of absorption peaks about 215 and 280 nm for all three prepared NCs (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Some studies have also been reported on poly(vinyl alcohol) thin films doped with a single rare-earth viz. Ho 3+ , Er 3+ , Sm 3+ , Eu 3+ and Ce 3+ (Kumar et al 1997;Seeta Rama Raju et al 2006;Abdel-Kader and Anwer 2007;Abdelaziz 2011). We have not come across studies on PVA matrices with combinations of different rare-earth dopant species.…”
Section: Introductionmentioning
confidence: 99%